Multicoagulant resistant pseudothrombocytopenia - Nausheen Waseem; Bashir Hanif; Jawaid Jabbar (Journal of the Pakistan Medical Association, 2021)
Pseudo thrombocytopenia is the estimation of low platelet counts by a Hematology analyzer in spite of lack of shortage in platelets. EDTA-induced pseudo thrombocytopenia, commonly seen in clinical practice, occurs mainly due to anti platelet antibodies. Pseudo thrombocytopenia is seen in normal healthy individuals as well as in other disorders like cardiovascular, liver, autoimmune diseases and malignancy. We are presenting a case of multi coagulant resistant dependent thrombocytopenia. The purpose of the case report is to review approaches to pseudo thrombocytopenia. The case has coagulant resistant dependent thrombocytopenia in association with Anasarca and was a known case of cardiomyopathy with severely dilated left atrium, left ventricle &right atrium. Keywords: Pseudo platelet aggregation, multicoagulant resistant thrombocytopenia, pseudo thrombocytopenia. Continuous...